Divorce and Its Practices Before A Religious Court; A Perspective Analysis of Islamic Legal - Qowiyul Iman, Rifqi; Joni, Joni (Alhurriyah, 2024)
This research discusses divorce in Islam, known as "talak." Articles 118 to 120 of the Compilation of Islamic Law regulate "talak raj’i" and "talak ba’in." The issue of divorce in religious courts remains a subject of debate, especially regarding the transfer of the right of divorce from the husband to the religious court judge. This research examines this issue from a jurisprudential perspective. The results indicate that in jurisprudence, "talak" means the dissolution and termination of a marriage bond. "Talak" is divided into "talak raj’i" and "talak ba’in," each with different legal implications. In Islam, "talak" can be pronounced in front of the wife or others. However, in the context of the state, compliance with government regulations is considered important as long as it does not violate Islamic law. The government establishes divorce regulations to maintain administrative order.   Penelitian ini membahas tentang perceraian dalam Islam, yang disebut talak. Pasal 118 s/d 120 Kompilasi Hukum Islam mengatur talak raj’i dan talak ba’in. Permasalahan talak di pengadilan agama masih menjadi perdebatan, terutama terkait pemindahan hak talak dari suami kepada hakim pengadilan agama. Penelitian ini melihat persoalan tersebut dari perspektif fikih. Hasilnya menunjukkan bahwa talak dalam fikih berarti melepaskan dan menghilangkan ikatan pernikahan. Talak terbagi menjadi talak raj’i dan talak ba’in, dengan implikasi hukum yang berbeda. Dalam Islam, talak dapat diucapkan di depan istri atau orang lain. Namun, dalam konteks negara, taat pada peraturan pemerintah dianggap penting, selama tidak melanggar hukum Islam. Pemerintah membentuk peraturan perceraian untuk menjaga ketertiban administrasi.